Dry Mopping vs. Saline Irrigation of Gallbladder Fossa After Bile Spillage During Laparoscopic Cholecystectomy: Randomized Control Trial - Bhatti, Dujanah S (Cureus, 2021)
Introduction The laparoscopic approach, as compared to open cholecystectomy, is still considered the gold standard, despite a higher incidence of micro insults. The most common approach to treat spilled biliary contents and lost stones in laparoscopic cholecystectomy is the retrieval of the stone through an open approach, or laparoscopically, ending with a peritoneal wash and aspiration. Material and methods We conducted a double-blinded randomized controlled trial. In the study group, patients with bile spillage during cholecystectomy underwent suction of all spilled bile and evacuation of all visible stones followed by dry mopping of the gallbladder fossa with gauze swab through an epigastric port. In the control group, after suction of all bile and visible stones, the gallbladder fossa was washed with 250 ml of saline, and fluid was aspirated through the epigastric port. Results Sixty patients were included (30 patients in each group), 71.6% were female and the rest were male. There was a statistically significant difference in pain scores between the two groups (p=0.001). The dry mopping group had lower pain scores as compared to the other group postoperatively. The incidence of the intraabdominal collection in both groups are statistically insignificant, however, port site infection and intraabdominal collection are higher in the control group (irrigation group). Conclusion Although there is not much literature on the best approach to biliary spillage in laparoscopic cholecystectomy. We believe that dry mopping had better postoperative patient outcome as compared to the saline wash.